2012
DOI: 10.1093/humupd/dmr050
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of age at menarche: a systematic review

Abstract: The reviewed studies laid a solid basis for future research on genetics of age at menarche. However, as yet specific genes for this trait have not been identified consistently in all ethnicities and types of studies. We suggest expanding the research to different ethnicities and propose several methodologies to increase the efficiency of studies in this area, including a systems approach, which combines existing high-throughput methods in a single pipeline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
79
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 124 publications
2
79
2
3
Order By: Relevance
“…The heredity factor is caused by influence of Sterol Regulatory Element Binding Protein (SREBP), Cytochrome P450 family 19 subfamily A polypeptide 1 (CYP19A1), Cytochrome P450 family 17 (CYP17), Estrogen Receptor α (ESR α), and GnRH receptor (GnRHR) gene that will affect quantities and activities of steroid hormones, such as GnRH, estrogen, and progesterone that stimulate process of menarche. 7,14,15 However, this study The correlation between subject's and biological mother's menarcheal age was the lowest correlation. This result is caused by other factors, such as nutritional intake before puberty, which could affect menarcheal age.…”
contrasting
confidence: 56%
“…The heredity factor is caused by influence of Sterol Regulatory Element Binding Protein (SREBP), Cytochrome P450 family 19 subfamily A polypeptide 1 (CYP19A1), Cytochrome P450 family 17 (CYP17), Estrogen Receptor α (ESR α), and GnRH receptor (GnRHR) gene that will affect quantities and activities of steroid hormones, such as GnRH, estrogen, and progesterone that stimulate process of menarche. 7,14,15 However, this study The correlation between subject's and biological mother's menarcheal age was the lowest correlation. This result is caused by other factors, such as nutritional intake before puberty, which could affect menarcheal age.…”
contrasting
confidence: 56%
“…It has been shown that around half of the variation in timing of menarche in the general population is attributable to genetic factors (Morris et al, 2011), and several genes associated with menarcheal age have been identified (Dvornyk and Ul-Haq, 2012). It is thought that there is also an element of genetic predisposition involved in radiosensitivity (Burrill et al, 2000;Gatti, 2001), and hence a potential explanation for our finding could be genetic linkage between loci associated with these two factors.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have demonstrated that SNPs are closely correlated with various menstrual disorders; for example, Dvornyk and Waqar-ul-Haq (2012) and He and Murabito (2014) identified a susceptibility gene associated with age at menarche. Taylor et al (2010) found that polymorphisms in the progesterone receptor gene are related to early age at menarche and a short menstrual cycle by analyzing the progesterone receptor gene and SNPs at 37 loci upstream and downstream of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that single nucleotidepolymorphisms (SNPs) are closely correlated with various menstrual disorders (Lussiana et al, 2008;Taylor et al, 2010;Biggs and Demuth, 2011;Chen et al, 2011;Dvornyk and Waqar-ul-Haq, 2012;Matsuzaka et al, 2012;He and Murabito, 2014). The PNPLA7 gene on chromosome 9 is primarily expressed in lipid and muscle as an insulin-regulated lysophospholipase, which is important for energy metabolism (Kienesberger et al, 2008) and the maintenance of axonal integrity (Kienesberger et al, 2009).…”
Section: Introductionmentioning
confidence: 99%